2006
DOI: 10.2337/db05-1543
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia Stimulates Coagulation, Whereas Hyperinsulinemia Impairs Fibrinolysis in Healthy Humans

Abstract: Type 2 diabetes and insulin resistance syndromes are associated with an increased risk for cardiovascular and thrombotic complications. A disturbed balance between coagulation and fibrinolysis has been implicated in the pathogenesis hereof. To determine the selective effects of hyperglycemia and hyperinsulinemia on coagulation and fibrinolysis, six healthy humans were studied on four occasions for 6 h: 1) lower insulinemic-euglycemic clamp, 2) lower insulinemic-hyperglycemic clamp, 3) hyperinsulinemic-euglycem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
161
2
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(176 citation statements)
references
References 40 publications
(35 reference statements)
9
161
2
4
Order By: Relevance
“…27 Hyperinsulinemia 28 and lower sex hormone-binding globulin 29 have been shown to impair fibrinolysis by directly enhancing the secretions of PAI-1. 28 PAI-1 is the principal inhibitor of fibrinolysis and may contribute to the development of thrombosis. 28,29 From this logic, we speculate that the women in our study population with PCOS between the ages of 18-24 years may have increased levels of PAI-1 compared with the other age groups and thus have the highest probability of VTE.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Hyperinsulinemia 28 and lower sex hormone-binding globulin 29 have been shown to impair fibrinolysis by directly enhancing the secretions of PAI-1. 28 PAI-1 is the principal inhibitor of fibrinolysis and may contribute to the development of thrombosis. 28,29 From this logic, we speculate that the women in our study population with PCOS between the ages of 18-24 years may have increased levels of PAI-1 compared with the other age groups and thus have the highest probability of VTE.…”
Section: Commentmentioning
confidence: 99%
“…28 PAI-1 is the principal inhibitor of fibrinolysis and may contribute to the development of thrombosis. 28,29 From this logic, we speculate that the women in our study population with PCOS between the ages of 18-24 years may have increased levels of PAI-1 compared with the other age groups and thus have the highest probability of VTE. Clinical studies are needed to test this hypothesis.…”
Section: Commentmentioning
confidence: 99%
“…In diabetes, TF expression is increased either directly by elevated glucose levels, 99 hyperinsulinemia, 100 or alternatively via activation of NFκB through advanced glycation end-products (AGE) 101 or reactive oxygen species (ROS). 102 AGE stimulates NFκB via their membrane receptor (RAGE) while ROS directly activate the transcription factor.…”
Section: Dmmentioning
confidence: 99%
“…It has been reported that hyperglycemia elevates coagulant activation markers, including thrombin antithrombin complexes and soluble tissue factor, whereas hyperinsulinemia inhibits fibrinolysis. 27 Sakamoto et al 28 examined alternation of platelet aggregability during the OGTT. Platelet aggregability, defined as the number of small platelet aggregations, was measured with a laser-light scattering method.…”
Section: Mechanisms By Which Acute Hyperglycemia Exacerbates Myocardimentioning
confidence: 99%